Facile synthesis of Ni/SiO2 catalyst by sequential hydrogen/air treatment: A superior anti-coking catalyst for dry reforming of methane. (September 2016) - Gao, X.Y.; Hidajat, K.; Kawi, S.
Graphical abstract: Abstract: A novel sequential treatment method (hydrogen treatment prior to air calcination) was used to prepare Ni/SiO2 catalysts by incipient wetness impregnation (IWI). This catalyst showed a uniform and small Ni particle size (d = 2.5 ± 0.8 nm) and a strong metal-support interaction (TR ≈ 670 °C), yielding an excellent catalytic performance (85% for CO2 conversion and 80% for CH4 conversion) with negligible metal sintering and no carbon deposition over 100-h dry reforming of methane (DRM) reaction. The first-step hydrogen treatment removed the oxygen radicals produced from the decomposition of Ni nitrate and the second-step air calcination stabilized Ni nanoparticles by forming Ni (phyllo)silicate structure. Therefore, the sequential calcination method produced small, uniform and highly dispersed Ni nanoparticles, strong metal-support interaction and excellent catalytic performances for DRM reaction.